ANALYSIS OF THE MAYANG TWIN TRADITION IN JAVANESE TRADITIONAL WEDDING CEREMONIES IN SIDODADI VILLAGE WONGSOREJO DISTRICT: Analisis Tradisi Kembar Mayang Dalam Upacara Pernikahan Adat Jawa di Desa Sidodadi Kecamatan Wongorejo - Jeany Salsa Bella; Sahru Romadloni; I Kadek Yudiana (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the Kembar Mayang Tradition, where each element has a profound meaning. The background of the study shows a gap in studies related to the Kembar Mayang tradition in Javanese traditional wedding ceremonies. Most previous studies have focused more on wedding rituals and have not discussed the Kembar Mayang tradition more specifically. The novelty of this study lies in the cultural transformation that occurs in the Kembar Mayang tradition. The purpose of this study is to analyze the implementation process, transformation of forms, and symbolic meaning of the Kembar Mayang tradition in Sidodadi Village, Wongsorejo District, Banyuwangi. The research findings show that there have been significant changes in the Kembar Mayang tradition in terms of materials, visual design, and community understanding. Traditional elements such as janur (young coconut leaves), banana stems, and symbolic figures such as birds, keris, and snakes are gradually being replaced by synthetic materials and simplified forms. Nevertheless, symbolic meanings such as harmony, prosperity, and the transition to a new life are still respected. However, there is a decline in philosophical awareness among the younger generation. This study emphasizes the importance of preserving the original form to maintain cultural values. This research contributes to the documentation of local heritage and highlights the need for cultural transmission amidst modernization. By focusing on previously unexplored areas, it provides new insights into the evolution of traditional symbols and reinforces the value of preserving cultural identity in the modern era.